Decreased Autophagic Activity in Triple-Negative Breast Cancer Cells upon Hydroxychloroquine and Thymoquinone Combination Treatment - Tuğcan Korak; Merve Gulsen Bal Albayrak; Sevinc Yanar; Gürler Akpınar; Murat Kasap (Hitit Medical Journal)

(untitled)
Objective: Autophagy plays a significant role in breast cancer tumorigenesis, including triple-negative breast cancer. Research indicates that hydroxychloroquine and thymoquinone modulate autophagy, potentially suppressing its activity. However, their combined effects on autophagy in triple-negative breast cancer remain unexplored. In this study, we investigated the potential anti-cancer and autophagy-modulating effects of hydroxychloroquine-thymoquinone combination on triple-negative breast cancer cells in vitro.Material and Method: The viability of MDA-MB-231 cells was evaluated after treatment with hydroxychloroquine (10-210 µM) and thymoquinone (5-45 µM) for 24 and 48 hours using the WST-1 assay. Combination effects were analyzed using the Chou-Talalay method with CompuSyn (v.10). Autophagic vesicles were visualized using an Autophagy Detection Kit and fluorescence microscopy to investigate their role in the decrease in cell viability. Statistical analysis was performed with GraphPad Prism (v.8.3.0).Results: At both 24- and 48-hour intervals post-treatment, a significant decrease in viability was observed for both hydroxychloroquine and thymoquinone treatments individually (p1). At 24 hours, favorable dose reduction effects were evident (dose reduction index >1), while the 48-hour results showed an unfavorable reduction (dose reduction index